2021
DOI: 10.3390/en14227487
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Slow Steaming Speed for Container Ships under the EU Emission Trading System

Abstract: Slow steaming is an operational measure in ocean-going vessels sailing at slow speeds. It can help climate mitigation efforts by cutting down marine fuel consumption and consequently reducing CO2 and other Greenhouse Gas Emissions (GHG). Due to climate change both the European Union (EU) and the International Maritime Organization (IMO) are analysing the inclusion of international shipping in the EU Emissions Trading System (ETS) in the near future or alternatively implementing a carbon tax. The paper proposes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Firstly, the annual income depends on the freight rates, loading capacity, and the number of round trips corresponding to each simulated ship speed. For container ships, it is assumed that the ship departed from the departure port loaded with 90% of its maximum capacity, while on the return trip, the ship is loaded with a reduced capacity depending on exist of empty containers onboard (Goicoechea and Abadie 2021 ). Therefore, the annual income corresponding to the simulated ship speed ( AI s , j ) is calculated as shown in Eq.…”
Section: Environmental and Economic Assessment Methodologymentioning
confidence: 99%
“…Firstly, the annual income depends on the freight rates, loading capacity, and the number of round trips corresponding to each simulated ship speed. For container ships, it is assumed that the ship departed from the departure port loaded with 90% of its maximum capacity, while on the return trip, the ship is loaded with a reduced capacity depending on exist of empty containers onboard (Goicoechea and Abadie 2021 ). Therefore, the annual income corresponding to the simulated ship speed ( AI s , j ) is calculated as shown in Eq.…”
Section: Environmental and Economic Assessment Methodologymentioning
confidence: 99%
“…Results indicated that the EU ETS can provide sufficient incentives for specific abatement measures. Goicoechea and Abadie (2021) examined the impact of the EU ETS on the optimal slow steaming speed of containerships. Containerships were chosen as they account for the largest proportion of GHG emissions.…”
Section: Including the Maritime Industry In The Eu Etsmentioning
confidence: 99%
“…There are some studies in the literature that focus on the application of slow steaming to meet the new regulations. Goicoechea and Abadie [17] studied the optimal use of slow steaming for container ships under the European Union Emission Trading System (ETS). They created a model that calculates the optimal speed to achieve minimum ETS carbon prices for container ships from 2000 to 20,000 TEU.…”
Section: Introductionmentioning
confidence: 99%